Clinical and morphological interaction of the combination of prokaryotes with fungal microflora in pathogenesis of infective endocarditis - O. A. Krykunov; V. P. Zakharova; R. V. Buryak; A. B. Koltunova; A. O. Rusnak; A. M. Khmelevsky (Ukrainian Journal of Cardiovascular Surgery, 2017)
The peculiarity of fungal infective endocarditis (IE) is manifestation of the disease on the background of significant damage of the patients’ immunological status, also due to corticosteroid or cytostatic therapy. Combination of fungal microflora with ESCAPE group microorganisms makes treatment of IE more complicated.Objectives: to investigate the clinical features of combination of prokaryotes with fungal microflora in the pathogenesis of IE.Materials and methods. The basis of this study was clinical data of 94 patients with active infective endocarditis, who were examined and surgically treated at the Amosov National Institute of Cardiovascular Surgery NAMS of Ukraine from 01.01.2014 to 01.12.2016 y.Results and discussion. The rates of gram-positive and gram-negative microorganisms were: 84 (89,4%) cases and 10 (10,6%) cases, respectively. Combination of prokaryotes and eukaryotes in the pathogenesis of infective endocarditis has been reported in 18 (19.1%) cases. Supplementation of fungal microflora was observed in cases of IE caused by Enterococcus spp. – 42.9% of cases. Among 22 cases of hospital-acquired IE in 8 (36.4%) cases, fungal mycelium was observed in the valve structures (X2=4.956, p=0.026).